ECOTOXICOLOGICAL EXAMINATION OF ACUTE TOXICITY OF SOME SPIROHYDANTOINS AND THEIR DERIVATIVES TOWARDS SEA LETTUCE (ULVA LACTUCA) - N. Marinov, Marin; H. Ganchev, Donyo; E. Marinova, Petja; N. Penchev, Plamen; V. Krustev, Stefan; R. Zlateva, Milena; I. Atanasova, Nadezhda; M. Stoyanov, Neyko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This article presents an ecotoxicological study of acute toxicity deleterious effect of cyclopentanespiro-5-hydantoin, cyclohexanespiro-5-hydantoin, cyclopentanespiro-5-(2,4-dithiohydantoin) and 1-aminocyclopentanecarboxylic acid towards Sea lettuce (Ulva lactuca) conducted in accordance with international standards adopted by the Organisation for Economic Co-operation and Development (OECD). Dose-response modeling was carried out by R language for Statistical Computing, drc package.